b - Bangladesh Sangbad' 71. (Dhaka : Bangladesh Sang-bad' 71 (BIDS'71), 2016)
Memoirs of the 1971 Bangladesh liberation war; a personal narrative.
In Bengali.
Keywords: Revolutionaries -- Bangladesh -- Biography; Bangladesh -- History -- Revolution, 1971 -- Personal narratives